Viral metagenomic survey of Caspian seals - Karamendin, Kobey; Goodman, Simon J.; Kasymbekov, Yermukhammet; Kumar, Marat; Nuralibekov, Sardor; Kydyrmanov, Aidyn (Frontiers in Veterinary Science, 2024)
IntroductionViral diseases of pinnipeds cause substantial mortality and morbidity and can influence population demography. Viral metagenomic studies can therefore play an important role in pinniped health assessments and disease surveillance relevant to both individual species and in a “One Health” context.MethodsThis study used a metagenomic approach with high throughput sequencing to make the first assessment of viral diversity in Caspian seals (Pusa caspica), the only marine mammal species endemic to the Caspian Sea.ResultsSequencing libraries from 35 seals sampled 2009–2020 were analysed, finding sequences from the viral families Circoviridae, Parvoviridae, Herpesviridae, Papillomaviridae, Picornaviridae, Caliciviridae, Cruciviridae, Anelloviridae, Smacoviridae, and Orthomyxoviridae, with additional detection of Adenoviridae via PCR. The similarity of viral contigs from Caspian seal to sequences recovered from other pinnipeds ranged from 63.74% (San Miguel sea lion calicivirus) to 78.79% (Seal anellovirus 4).DiscussionSome findings represent novel viral species, but overall, the viral repertoire of Caspian seals is similar to available viromes from other pinnipeds. Among the sequences recovered were partial contigs for influenza B, representing only the second such molecular identification in marine mammals. This work provides a foundation for further studies of viral communities in Caspian seals, the diversity of viromes in pinnipeds more generally, and contributes data relevant for disease risk assessments in marine mammals.